The Experience of Foreign Countries in the Monetary System Development - ORYNBASSAROVA, Yerkenazym D.; KARIBAEV, Yerkebulan S. (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
This study aims in analyzing the world experience in the development of monetary systems along with the subsequent elaboration of recommendations related to the development of the Kazakh monetary policy. The authors used general theoretical methods (comparison, generalization and analysis). The study analyzes the methods, models and tools currently used by the central banks of the developed economies. Regulatory mechanism involves forecasting methods, regulation tools related to cash and non-banking operations and specific forms of control over the money supply dynamics, bank interest rates, bank liquidity at the macro and micro level. The paper identifies their strengths and weaknesses, as well as the possibilities of their practical use in the Kazakh monetary market regulations. The macroeconomic model of monetary policy implementation is considered with regard to the viewpoints, expressed by the supporters of monetarism and Keynesianism. The novelty of this research lies in analyzing the experience of the developed economies in the context of highlighting not only general and specific features related to the development of monetary systems of these countries, but also in terms of their applicability and improvement in other countries, having smaller resource base and weaker experience in good governance (in particular, Kazakhstan).
Keywords: monetary policy; monetary system; monetarism; Keynesian model; economic growth